Предмет: Математика,
автор: sonya13452
Упростите выражение
a)3(x+1)+(x-1)
b)3x(x-2)-5x(x+3)
v)13(6b-1)-6(13b-1)
g)p(p^2-2a)+a(2p-a^2)
Ответы
Автор ответа:
1
3(х+1)+(х-1)=3х+3+х-1=4х+2
3х(х-2)-5х(х+3)=3х^2 -6х-5х^2 -15х=-2х^2 -21х
13(6b-1)-6(13b-1)=78b-13-78b+6=-7
p(p^2 -2a)+a(2p-a^2)=p^3 -2ap+2ap-a^3=p^3 -a^3
Похожие вопросы
Предмет: Алгебра,
автор: stanetskiyivan
Предмет: Алгебра,
автор: Bogdan28822
Предмет: Русский язык,
автор: liliadiulina
Предмет: Математика,
автор: NORManChikc
Предмет: Литература,
автор: KynGyTVoin